2024
DOI: 10.1038/s41598-024-57823-3
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and assessment of antibacterial and antioxidant activities of silver nanoparticles utilizing Cassia occidentalis L. seed

Arvind Arya,
Pankaj Kumar Tyagi,
Sachin Bhatnagar
et al.

Abstract: This research explores the eco-friendly synthesis of silver nanoparticles (AgNPs) using Cassia occidentalis L. seed extract. Various analytical techniques, including UV–visible spectroscopy, transmission electron microscopy (TEM), scanning electron microscopy (SEM), X-ray diffraction (XRD), and energy dispersive X-ray spectroscopy (EDX), were employed for comprehensive characterization. The UV–visible spectra revealed a distinct peak at 425 nm, while the seed extract exhibited peaks at 220 and 248 nm, indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 92 publications
(79 reference statements)
1
0
0
Order By: Relevance
“…At the same time, Zhu et al [32] identified a direct correlation between the total polyphenol content and the DPPH scavenging ability of grape pomace extracts; this correlation could also explain the differences recorded in our study regarding the antioxidant potential of the two extracts. Also, phytosynthesized silver nanoparticles have commonly been found by other authors to significantly increase the antioxidant activity of the parent extract [33] in a silver-concentration-dependent manner [34], which is in good agreement with the results of the present study. The DPPH antioxidant assay revealed an increase in the antioxidant potential of the phytosynthesized nanoparticles compared with the parent extracts, as well as a superior antioxidant potential of the extract obtained by the microwave-assisted method (compared with the temperature extraction method).…”
Section: Discussionsupporting
confidence: 93%
“…At the same time, Zhu et al [32] identified a direct correlation between the total polyphenol content and the DPPH scavenging ability of grape pomace extracts; this correlation could also explain the differences recorded in our study regarding the antioxidant potential of the two extracts. Also, phytosynthesized silver nanoparticles have commonly been found by other authors to significantly increase the antioxidant activity of the parent extract [33] in a silver-concentration-dependent manner [34], which is in good agreement with the results of the present study. The DPPH antioxidant assay revealed an increase in the antioxidant potential of the phytosynthesized nanoparticles compared with the parent extracts, as well as a superior antioxidant potential of the extract obtained by the microwave-assisted method (compared with the temperature extraction method).…”
Section: Discussionsupporting
confidence: 93%